1980
DOI: 10.2136/sssaj1980.03615995004400040034x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Properties of a Newly Cleared Tropical Alfisol as Affected by Mulching

Abstract: Rapid deterioration in soil physical properties following deforestation for arable land use adversely affects crop production from soils in the humid and subhumid tropics. This investigation was conducted to determine whether the rate of deterioration can be minimized by the use of crop residue mulches. Changes in soil properties of a newly cleared tropical Alfisol resulting from mulch rates of 0, 2, 4, 6, and 12 tons ha−1 season−1 of rice (Oryza sativa) straw were investigated from 1976 to 1977. Total porosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

1984
1984
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(41 citation statements)
references
References 0 publications
1
38
0
2
Order By: Relevance
“…No-tillage production results in changes in soil physical properties, including increases in soil organic matter content (Douglas and Goss, 1982), aggregate stability (Heard et al, 1988) and macroporosity (Lal et al, 1990). The changes may be detrimental, neutral or beneficial for crop growth and yield, depending on the soil texture and structure (Dick and VanDoren, 1985) and on 84 climatic factors such as rainfall (Morrison et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…No-tillage production results in changes in soil physical properties, including increases in soil organic matter content (Douglas and Goss, 1982), aggregate stability (Heard et al, 1988) and macroporosity (Lal et al, 1990). The changes may be detrimental, neutral or beneficial for crop growth and yield, depending on the soil texture and structure (Dick and VanDoren, 1985) and on 84 climatic factors such as rainfall (Morrison et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Porosity characteristics differ among tillage systems (Benjamin 1993) and nowadays, study on the soil porosity of different tillage treatment is one of the hotspots in tillage research. Previous researches showed that straw returning could increase the total porosity of soil (Lal et al 1980) while minimal and no tillage would decrease the soil porosity for aeration, but increase the capillary porosity; as a result, it enhances the water capacity of soil along with bad aeration of soil (Wang et al 1994, Glab andKulig 2008). However, Børresen (1999) found that the effects of tillage and straw treatments on the total porosity and porosity size distribution were not significant.…”
mentioning
confidence: 97%
“…Macroporosity and total porosity at the soil surface. Lal et al, 1980;Parker et al, 1992;De Vleeschauwer et al, 1980;Tollner et al, 1984. Carpenedo & Mielniczuk, 1990Hulugalle, 1994. Size and ammount of water-stable aggregates.…”
Section: Methodsmentioning
confidence: 99%